2021
DOI: 10.2224/sbp.9643
|View full text |Cite
|
Sign up to set email alerts
|

Charismatic leadership and millennial employee innovation performance relationship mediated by employees' leadership, professional, and organizational identification

Abstract: Using leadership behavior and social identity theories, we conducted an empirical study with 361 millennial employees to explore the mechanisms underlying the impact of charismatic leadership on employee innovation performance in the Chinese context, and to understand the serial mediation effects of employees' leadership, professional, and organizational identification. The results show that charismatic leadership had a significant positive effect on millennial employee innovation performance and that this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…e research results demonstrated the substitution of human resource management practice and authorized leadership in knowledgeintensive teams. Zhao et al [39] examined the relationship between employees' leadership, professional and organizational identity, and applied leadership behavior and social identity theory. e results showed that leadership behavior and social identity theory significantly impacted the mechanism of EIP.…”
Section: Effect Of Knowledge-based Employee Incentive Mechanism (Eim)mentioning
confidence: 99%
“…e research results demonstrated the substitution of human resource management practice and authorized leadership in knowledgeintensive teams. Zhao et al [39] examined the relationship between employees' leadership, professional and organizational identity, and applied leadership behavior and social identity theory. e results showed that leadership behavior and social identity theory significantly impacted the mechanism of EIP.…”
Section: Effect Of Knowledge-based Employee Incentive Mechanism (Eim)mentioning
confidence: 99%
“…Charismatic leaders demonstrate exemplary acts that followers construe as entailing great personal risk, dedication to the vision and self-sacrifice, through which, they can fuel followers’ motivation and trust (Conger et al ., 2000). Consequently, charismatic leadership may yield employees’ attachment to the leader, their collective identity and their engagement and contribution to collective goals (Xenikou, 2014; Zhao et al ., 2021).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Charismatic leadership has been empirically reported to exert beneficial effects on employees, teams and organizations. Research has revealed that charismatic leaders can foster employees’ affective identification (Xenikou, 2014), intrinsic motivation, tacit knowledge-sharing behavior (Shao et al ., 2017) and innovation performance (Zhao et al ., 2021). Charismatic leadership has also been observed exerting positive impacts on team or organizational outcomes such as team psychological capital (Uen et al ., 2021), team efficacy, team control (McClelland et al ., 2014), work team innovative behavior (Le Blanc et al ., 2021), psychological safety climate (Shao et al ., 2017), team performance (Tims et al ., 2013), firms’ environmental performance and financial performance (Zhang and Wei, 2021).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Some scholars have considered it a mediating variable between inclusive leadership and employee voice or prosocial behavior ( Khattak et al, 2022 ), or between moral leadership and inhibitory feedback. Furthermore, existing studies take identification with a leader as a moderating variable between charismatic leadership and innovation performance of employees ( Zhao et al, 2021 ). Current research has mainly used identification with leaders as a mediating variable, while the amount of literature on identification with leaders as a moderating variable is small and needs to be expanded.…”
Section: Literature Reviewmentioning
confidence: 99%